2012
DOI: 10.5194/acpd-12-8465-2012
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Global and regional trends of aerosol optical depth over land and ocean using SeaWiFS measurements from 1997 to 2010

Abstract: Both sensor calibration and satellite retrieval algorithm play an important role in the ability to determine accurately long-term trends from satellite data. Owing to the unprecedented accuracy and long-term stability of its radiometric calibration, the SeaWiFS measurements exhibit minimal uncertainty with respect to sensor calibration. In this study, we take advantage of this well-calibrated set of measurements by applying a newly-developed aerosol optical depth (AOD) retrieval algorithm over land and oce… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
129
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(146 citation statements)
references
References 33 publications
17
129
0
Order By: Relevance
“…A trend analysis of the SeaWiFS data, in conjunction with AERONET and other satellite datasets, has been performed by Hsu et al (2012).…”
Section: Regional Comparisonsmentioning
confidence: 99%
“…A trend analysis of the SeaWiFS data, in conjunction with AERONET and other satellite datasets, has been performed by Hsu et al (2012).…”
Section: Regional Comparisonsmentioning
confidence: 99%
“…Fine particles with aerodynamic diameters of 2.5 µm and less (PM 2.5 ) are the most effective factor for visibility impairment and fugitive dust) and regional emissions under the influence of different meteorological conditions, especially in spring and winter (Hou et al, 2011;Long et al, 2014). In recent years, haze events in Shanghai have been widely concerned and intensely studied (Hsu et al, 2012;Cheng et al, 2013;Lin et al, 2014). Cheng et al (2013) summarized that visual range in the Yangtze River Delta endured a reduction from 13.2 to 10.5 km from 1980 to 2000.…”
Section: Introductionmentioning
confidence: 99%
“…Cheng et al (2013) summarized that visual range in the Yangtze River Delta endured a reduction from 13.2 to 10.5 km from 1980 to 2000. Hsu et al (2012) analyzed the global and regional trends of aerosol optical depth over land and ocean based on remote sensing products from 1997 to 2010. Fu et al (2008) showed that the hourly PM 2.5 and PM 10 concentrations of the heavy haze days in Shanghai could reach as high as 466 and 744 µg m -3 on 19 January 2007, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The Advanced Along Track Scanning Radiometer (AATSR) aboard Envisat can also provide AOD products with high nadir spatial resolution (1 km × 1 km) [14][15][16][17]. Meanwhile, the Seaviewing Wide Field-of-view Sensor (SEAWIFS) aboard GeoEye's OrbView-2 can provide AOD data over the globally ocean with a spatial resolution of 9 km × 9 km [18][19][20]. Long-term daily and monthly AOD records can also be obtained from the Advanced Very High Resolution Radiometer (AVHRR) aboard on TIROS-N and NOAA series with nadir spatial resolution of 1.1 km × 1.1 km [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%